Office Administration Management: Competency Based Training - Agustin H P; Yuniorita Indah Handayani; Musaiyadi Musaiyadi (Trescode Green Organization, 2024)
This activity aims to evaluate the effectiveness of office administration training and mentoring activities in Jember Regency, Indonesia, in improving the skills of the young generation ready for work. The activity was carried out for two months by a team of lecturers from the Mandala Institute of Technology and Science, covering the planning, implementation, and qualitative evaluation stages. The training included theoretical modules and direct mentoring by lecturers, with a focus on office administration, information technology, and communication skills. The results of the training activities showed a significant increase in administrative skills and the application of information technology by participants. Intensive mentoring also helped participants overcome practical challenges in the work environment. An important implication in the form of positive results from this activity supports previous evidence that structured training and direct mentoring are effective in preparing young people to face the demands of the modern workplace. These implications can help in designing similar programs in the future to improve work readiness at the local and national levels.